Learning to Optimize Meter Reading Routes in Billing Management Problems in the Balata Regional Unit - Muchtar, Gatot Mochamad; Simanjuntak, Rinovia Mery Garnierita (Journal La Multiapp, 2025)
Meter reading route optimization is a significant challenge in the billing management of the State Electricity Company (PLN). This study evaluates the potential of the Traveling Salesman Problem (TSP) in overcoming this problem. By applying TSP to the Balata Region case study, this study aims to find a more efficient and effective route solution. The results of the study are expected to reduce operational costs, increase officer productivity, and increase customer satisfaction. It is hoped that TSP can be an attractive alternative for electricity companies in optimizing the meter reading process.